Vinpocetine protects against the development of experimental abdominal aortic aneurysms. Issue 22 (27th November 2020) - Zhang, Chongyang; Hsu, Chia George; Mohan, Amy; Shi, Hangchuan; Li, Dongmei; Yan, Chen
Abstract: Abdominal aortic aneurysm (AAA), commonly occurring in the aged population, is a degenerative disease that dilate and weaken infrarenal aorta due to progressive degeneration of aortic wall integrity. Vinpocetine, a derivative of alkaloid vincamine, has long been used for cerebrovascular disorders and cognitive impairment in the aged population. Recent studies have indicated that vinpocetine antagonizes occlusive vascular disorders such as intimal hyperplasia and atherosclerosis. However, its role in vascular degenerative disease AAA remains unexplored. Herein, we determined the effect of vinpocetine on the formation of AAA as well as the intervention of pre-existing moderate AAA. AAA was induced by periaortic elastase application in C57BL/6J mice. Systemic vinpocetine treatment was applied daily via intraperitoneal injection. We showed that vinpocetine pre-treatment remarkably attenuated aneurysmal dilation assessed by diameter and volume. More importantly, vinpocetine also significantly suppressed the progression of pre-existing moderate AAA in a post-intervention model. Vinpocetine improved multiple cellular and molecular changes associated with AAA, such as elastin degradation, media smooth muscle cell depletion, collagen fibers remodeling and macrophage infiltration in aneurysmal tissues. Vinpocetine potently suppressed tumor necrosis factor-α-induced nuclear factor kappa-light-chain-enhancer of activated B cells activation and proinflammatory mediator expression in primary cultured macrophages in vitro, as well as in the aorta wall in vivo, suggesting vinpocetine conferred anti-AAA effect at least partially via the inhibition of inflammation. Taken together, our findings reveal a novel role of vinpocetine in AAA formation, development and progression. Given the excellent safety profile of vinpocetine, the present study suggests vinpocetine may be a novel therapeutic agent for AAA prevention and treatment.